Reading Comprehension Level and Academic Performance of College Students in Their Mathematics Course - Galang, Ruby T.; Arrozal, Jocelyn Y.; Regala, Angelo; Manlutac, Anne Canlyn (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
Reading is regarded as a vital skill in attaining proficiency and widening knowledge in different subjects. The research aimed to establish the relationship of reading comprehension to academic performance in Mathematics. The respondents were the freshmen students in specified Math in the Modern World course. This study employed descriptive quantitative design. A researcher-made instrument which underwent experts’ validation and reliability test was used in determining the comprehension level in reading of the respondents. The results specified that positive correlation of reading comprehension and academic performance exists. Based on the results, there exists a highly significant difference between the reading comprehension level of the participants and their academic performance in their math courses. Moreover, with the generated value of .298, it can be inferred that that there is a positive relationship between the variables. This means if one variable increases the other variable moderately increases.